Pelvic fixation in surgical correction of neuromuscular scoliosis - Mazda Farshad (North American Spine Society Journal, 2022)
Background: Surgical correction of neuromuscular scoliosis can be associated with high complication rates, including such associated with pelvic fixation. Up to now it is debated whether and when to include the pelvis into the fusion construct. Therefore, we aimed to illuminate when pelvic fixation is beneficial in surgical correction of neuromuscular scoliosis. Methods: A prospective cohort of 49 patients (mean age 13 ± 3 y, 63% females, follow up 56 months, range 24–215) who underwent correction of neuromuscular scoliosis including S1/the ileum (n = 18) or without (n = 31) pelvic fixation were included. The outcome was measured with analysis of radiological parameters, clinical improvement and complication/revision rates. Subgroup analysis was performed to find if non-ambulatory patients with gross motor function classification system (GMFCS) levels >III, with larger scoliotic curves (>60°) and moderate pelvic obliquities up to 35° benefit from pelvic fixation. Results: There was no significant difference in complications when comparing patients with (9 out of 18 patients, 50%) or without (9 out of 31 patients, 29%) fixation to the pelvis (p = .219). Wheelchair bound patients (GMFCS >III) with cobb angles greater than 60° and pelvic obliquity less than 35° (n = 20) revealed no differences in amount of clinical improvement of ambulation with (n = 9) or without (n = 11) pelvic fixation (p: n.s.). And even complication or revision rates where not different in those two groups. Conclusion: Pelvic fixation does not seem obligatory in wheelchair bound patients per definition. Even with pelvic obliquities up to 35° and large scoliotic curves >60°, avoiding pelvic fixation does not result in higher revision rate or worse clinical outcomes.